2023
DOI: 10.1111/iep.12468
|View full text |Cite
|
Sign up to set email alerts
|

miR‐144‐3p represses hepatocellular carcinoma progression by affecting cell aerobic glycolysis via FOXK1

Abstract: Hepatocellular carcinoma (HCC) is a form of malignancy that develops frequently and is ranked fourth in the global causes of cancer deaths. 1 Cirrhosis is the predominant risk factor for HCC, which is caused by factors such as hepatitis B, hepatitis C infection, and excessive alcohol consumption. 2 Conventional treatments of HCC include partial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Cao et al [21] have found that miR-144-3p is highly expressed in thyroid cancer tissue and the silencing miR-144-3p can inhibit cell proliferation, invasion and promote cell apoptosis. Also, previous research have proven that miR-144-3p can inhibit biological behaviors like the proliferation, migration and invasion of tumor cells [21,22]. Despite extensive reporting on miR-144-3p in tumors, limited investigations have been conducted regarding its presence in colon carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al [21] have found that miR-144-3p is highly expressed in thyroid cancer tissue and the silencing miR-144-3p can inhibit cell proliferation, invasion and promote cell apoptosis. Also, previous research have proven that miR-144-3p can inhibit biological behaviors like the proliferation, migration and invasion of tumor cells [21,22]. Despite extensive reporting on miR-144-3p in tumors, limited investigations have been conducted regarding its presence in colon carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, FOXK2 exerts tumor-suppressive functions in prostate cancer and medulloblastoma ( 23 ). Additionally, FOXK1 appears to regulate expression of genes involved in glucose metabolism, whereas FOXK2 regulates the DNA damage response and its repair ( 34 , 35 ).…”
mentioning
confidence: 99%